2012
DOI: 10.1098/rsob.120078
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative single-molecule microscopy reveals that CENP-A Cnp1 deposition occurs during G2 in fission yeast

Abstract: The inheritance of the histone H3 variant CENP-A in nucleosomes at centromeres following DNA replication is mediated by an epigenetic mechanism. To understand the process of epigenetic inheritance, or propagation of histones and histone variants, as nucleosomes are disassembled and reassembled in living eukaryotic cells, we have explored the feasibility of exploiting photo-activated localization microscopy (PALM). PALM of single molecules in living cells has the potential to reveal new concepts in cell biology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
143
2
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 148 publications
(155 citation statements)
references
References 42 publications
6
143
2
4
Order By: Relevance
“…Single molecule counting-PALM is used to determine protein stoichiometry when single step photobleaching is not feasible (such as high density of proteins) [11][12][13][14] . Fluorescent proteins are photoactivated one at a time, detected and subsequently photobleached (Fig.…”
Section: Single Molecule Counting-palmmentioning
confidence: 99%
See 1 more Smart Citation
“…Single molecule counting-PALM is used to determine protein stoichiometry when single step photobleaching is not feasible (such as high density of proteins) [11][12][13][14] . Fluorescent proteins are photoactivated one at a time, detected and subsequently photobleached (Fig.…”
Section: Single Molecule Counting-palmmentioning
confidence: 99%
“…These probes can be activated in sparse numbers over time such that their images are optically resolvable and can be precisely localized 4 . These techniques have been exploited to image sub-cellular structures [5][6][7] , visualize protein (co)-organization [8][9][10] and quantify protein stoichiometry [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies made progress in quantifying single-molecule superresolution microscopy data by correcting for dye blinking (25)(26)(27)(28). Other approaches calculated averaged spatial distributions of an ensemble of signaling complexes (33,38) or determined high mEos2 molecule numbers using an average number of blinking events (39). One persistent problem is the strong environmental dependence of the photophysical parameters required for blink correction and the fraction of unobserved fluorophores.…”
Section: Challenges For Counting Single Molecules With Superresolutionmentioning
confidence: 99%
“…Two independent investigations have led to somewhat different conclusions for CENP-A/ Cnp1 deposition in fission yeast. One suggests that two redundant pathways operate in S or G 2 phase, respectively (24), whereas a recent study concludes that Cnp1 is replenished exclusively in G 2 phase (25). Overall, a common feature seen in various species is that CENP-A replenishment in many cases may occur without a tight junction with DNA replication (26).…”
mentioning
confidence: 99%
“…Multiple lines of investigation, using quantitative fluorescence microscopy, have shown that on average, over 50% of total nucleosomes in centromeres contain Cnp1 (25,34), although a separate study showed a much higher number of Cnp1 molecules residing in centromeres, exceeding the full capacity of centromeric chromatin (35) (see Fig. 2 for details).…”
mentioning
confidence: 99%